2011
DOI: 10.1016/j.comppsych.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Illness experience and reasons for nonadherence among individuals with bipolar disorder who are poorly adherent with medication

Abstract: Aim Nonadherent individuals are the most likely to avoid participating in research studies, thus limiting potential opportunities to develop evidence-based approaches for adherence enhancement. This mixed-method analysis evaluated factors related to adherence among 20 poorly adherent community mental health clinic patients with bipolar disorder (BD). Methods Illness experience was evaluated with qualitative interview. Quantitative assessments measured symptoms (Hamilton Depression Rating Scale, Young Mania R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
2
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 31 publications
8
73
2
10
Order By: Relevance
“…Low social support increases development of the disease, and decreases recovery chance (51). Sajatovic et al (52) reported that supportive social networks, and problems in access to treatment might affect the compliance, and it was determined in the study that there were individuals against drug treatment in nearly 1/3 of nuclear social network of patients. Oral et al (16) performed a study on bipolar patients, and reported that there were significantly more individuals in social networks of patients who could comply with treatment than the ones who could not.…”
Section: Discussionmentioning
confidence: 99%
“…Low social support increases development of the disease, and decreases recovery chance (51). Sajatovic et al (52) reported that supportive social networks, and problems in access to treatment might affect the compliance, and it was determined in the study that there were individuals against drug treatment in nearly 1/3 of nuclear social network of patients. Oral et al (16) performed a study on bipolar patients, and reported that there were significantly more individuals in social networks of patients who could comply with treatment than the ones who could not.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment compliance is one of the prognostic predictors in bipolar disorder (Velligan, 2010). The influencing elements in low compliance are alcohol and drug abuse consumption, severity of symptoms, young age, negative attitude to treatment, insufficient information about the problem and inaccessibility of medical services (Sajatovic, 2011).…”
Section: Psychoeducation For Bipolar Mood Disordermentioning
confidence: 99%
“…Adherence enhancement. Considering the fact that the most important cause of relapse in bipolar patients is non-adherence (Guscott & Taylor, 1994;Silverstone et al, 1998) and common reasons of non-adherence are incorrect information, fear of side effects and dependency, and lack of information about the illness and the necessity of treatment (Sajatovic et al, 2011), adherence enhancement is one of the main points of psychoeducation sessions. Many patients are not capable to follow the correct instruction of taking medicine and this has been pointed out as the main cause of non-adherence (Sajatovic et al, 2011); thus it is necessary that patient is kept informed about different kinds of drugs for bipolar disorder, the ways of monitoring their effects, and the side effects of each, so that they would know how to manage side effects and also gain insight to disadvantage of discontinuation of medication.…”
Section: The Content Of Psychoeducation Program For the Patientmentioning
confidence: 99%
“…Forgetting to take medication is a common reason that has been consistently associated with nonadherence. 46,67,105,[114][115][116] Patient medication beliefs and how these beliefs affect medication adherence have also been extensively studied. 4,41,42,44,88,89,[117][118][119][120][121][122] One of the most commonly used adherence scales, the Beliefs about Medicines Questionnaire-Specific (BMQ-S), elicits beliefs about the necessity of medicines and concerns about medicines.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…214 As discussed in Section 1.4, patients are non-adherent due to many different reasons, and may be subjected to different types of non-adherence concurrently (Section 1.2.4). 1,18,87,89,90,93,96,100,114,115,145,147 Both are important to consider when selecting an appropriate intervention to address non-adherence. 33 Identifying the reasons for nonadherence facilitates a strategy to address these reasons, which can be described as a tailored intervention.…”
Section: Self-report Adherence Scalesmentioning
confidence: 99%